Anthocyanin Phytochemical Profiles and Anti‐oxidant Activities of Vitis candicans and Vitis doaniana. Issue 5 (9th July 2013) - la, Alexander Acevedo De; Hilbert, Ghislaine; Mengin, Virginie; Rivière, Céline; Ollat, Nathalie; Vitrac, Caroline; Bordenave, Louis; Decroocq, Stéphane; Delaunay, Jean‐Claude; Mérillon, Jean‐Michel; Monti, Jean‐Pierre; Gomès, Eric; et al.
ABSTRACT Introduction Grapes are one of the most important fruit crops in the world. The quality of red grape berries greatly depends on skin colour, mainly due to the anthocyanin profile. Today, the American Vitis species have the greatest potential for breeding work. They have multiple resistance properties in comparison with Vitis vinifera but little is known about their anthocyanin content. Objective To determine the anti‐oxidant properties and anthocyanin profile of two American species, Vitis candicans and Vitis doaniana, by using LC–MSn and LC–NMR. Methods Grape extracts were prepared by extraction of berry skins with acidified methanol. The complete structure elucidation of the individual anthocyanins was performed with LC–MSn, LC–NMR and NMR experiments. Individual anthocyanins in the extracts were quantified by using malvidin glucoside as external standard. The anti‐oxidant activities of grape skin extracts were evaluated by using 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging and oxygen radical absorbance capacity (ORAC) assays. Results By using LC–MSn and LC–NMR experiments, 30 anthocyanins were identified and quantified in the two Vitis species, including two new cis‐p‐coumaroyl derivatives. Vitis candicans and V. doaniana showed significant differences in their anthocyanin profile. These two Vitis species possess low‐to‐medium anti‐oxidant activities in comparison with V. vinifera. Conclusion The profiles of 30 anthocyanins were established unambiguously in two American Vitis species. Copyright © 2013 John Wiley & Sons, Ltd.